Sustainable Communities and the Challenge of Environmental Justice. - Agyeman, Julian (NYU Press, 2005)
Popularized in the movies Erin Brockovich and A Civil Action, "environmental justice" refers to any local response to a threat against community health. In this book, Julian Agyeman argues that environmental justice and the sustainable communities movement are compatible in practical ways. Yet sustainability, which focuses on meeting our needs today while not compromising the ability of our successors to meet their needs, has not always partnered with the challenges of environmental justice. Sustainable Communities and the Challenge of Environmental Justice explores the ideological difference.